2022
DOI: 10.3389/fmolb.2022.963455
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Eosinophil-Associated Genes can Serve as a Reliable Predictor of Bladder Urothelial Cancer

Abstract: Background: Numerous studies have shown that infiltrating eosinophils play a key role in the tumor progression of bladder urothelial carcinoma (BLCA). However, the roles of eosinophils and associated hub genes in clinical outcomes and immunotherapy are not well known.Methods: BLCA patient data were extracted from the TCGA database. The tumor immune microenvironment (TIME) was revealed by the CIBERSORT algorithm. Candidate modules and hub genes associated with eosinophils were identified by weighted gene co-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…We explored the association of risk signature and TMB in this study and found that risk signature and TMB had some synergistic effects in predicting patient survival. Previous studies have found that TMB can be used to predict the efficacy of immune checkpoint inhibitor therapy ( Snyder et al, 2014 ; Hugo et al, 2016 ; Carbone et al, 2017 ; Liang et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ). It has also been found that TMB is associated with the prognosis of diffuse glioma ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We explored the association of risk signature and TMB in this study and found that risk signature and TMB had some synergistic effects in predicting patient survival. Previous studies have found that TMB can be used to predict the efficacy of immune checkpoint inhibitor therapy ( Snyder et al, 2014 ; Hugo et al, 2016 ; Carbone et al, 2017 ; Liang et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ). It has also been found that TMB is associated with the prognosis of diffuse glioma ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if there was a correlation between RS and TICs, we measured immune cell infiltration in TME using seven different methods including XCELL, TIMER, QUANTISEQ, MCPcounter, EPIC, CIBERSORT, and CIBERSORT-ABS to evaluate the immune infiltrating situation ( Xu et al, 2022b ). Based on gene expression data, the ESTIMATE algorithm determines how many stromal cells and immune cells are present in a tumor sample using the stromal score and immune score.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we used a variety of sources to analyze the correlation between IMPDH1 and immune cells in TME. Immune cells are able to regulate and predict the process of immunotherapy through related hub genes, including a variety of immune cells in the process of tumor immunity, such as CD8 + T cells, tumor-associated macrophages, natural killer cells, eosinophils, etc (41)(42)(43). The strongest relationship suggested that IMPDH1 might play an immunoregulatory role through CD8 + T lymphocytes and monocyte-macrophages.…”
Section: ) Sensitizing Immune C H E C K P O I N T I N H I B I T O R S...mentioning
confidence: 99%